Additional considerations on electrolysis in electromembrane extraction - Slampova, Andrea; Kuban, Pavel; Bocek, Petr (Journal of Chromatography A, 2016)
•Electrolysis can be controlled by proper selection of EME operational parameters.•Stable long-term EME performance is ensured for optimized acceptor solutions.•Saturation of acceptor solutions with analytes has no effect on their back-extraction.•Electrolytically produced ions are not transferred across selective phase interfaces. Optimized acceptor solutions, which eliminate electrolytically induced variations in their pH values, have been shown to improve electromembrane extraction (EME) performance. Acceptor solutions containing 500mM formic acid (pH 1.97) ensured stable EME process for three basic drugs extracted at 50V across 1-ethyl-2-nitrobenzene and constant extraction recoveries (66–89%) were achieved for 40–80min EMEs. Back-extraction of analytes into donor solutions has been eliminated by application of optimized acceptor solutions, moreover, saturation of acceptor solutions with analytes had no additional effect on their back-extraction; the presence of up to 300-fold excess of analytes in optimized acceptor solutions led to slightly reduced but stable enrichment of analytes over the entire extraction time. Stable EME performance has been also achieved for extractions into 100mM HCl, note however, that seriously compromised performance of subsequent capillary electrophoretic analyses has been observed due to high conductivities of resulting acceptor solutions. Electrolytically produced H+ and OH− ions have mostly remained in corresponding operating solutions, have determined their final pH values and have not been subjects of EME transfers across selective phase interfaces as was experimentally verified by pH measurements of anolytes and catholytes at various EME times.